2015
DOI: 10.1007/s10750-015-2466-z
|View full text |Cite
|
Sign up to set email alerts
|

Foraging specialisms influence space use and movement patterns of the European eel Anguilla anguilla

Abstract: (2015) 'Foraging specialisms inuence space use and movement patterns of the European eel Anguilla anguilla. ', Hydrobiologia., 766 (1). pp. 333-348. Further information on publisher's website:http://dx.doi.org/10.1007/s10750-015-2466-z Publisher's copyright statement:The nal publication is available at Springer via http://dx.doi.org/10.1007/s10750-015-2466-z Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 62 publications
1
47
0
Order By: Relevance
“…Previous studies reported that possible posthandling effects influence eel behaviour in the first time period after release (Barry et al., ; Simon et al., ). Accordingly, Barry et al.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Previous studies reported that possible posthandling effects influence eel behaviour in the first time period after release (Barry et al., ; Simon et al., ). Accordingly, Barry et al.…”
Section: Discussionmentioning
confidence: 98%
“…Accordingly, Barry et al. () excluded all detections recorded 4 days after release in their study. In the current study, high movement activities were observed within the first 10 hr compared with the remaining period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…g . using different habitats, foraging areas or specializing in different prey types (Schindler et al ., ; Iguchi et al ., ; Barry et al ., ). Such specialization could then result in geographically small‐scaled phenotypic differences, such as variation in growth or body condition.…”
Section: Introductionmentioning
confidence: 99%